2022
DOI: 10.1002/cphc.202100809
|View full text |Cite
|
Sign up to set email alerts
|

Narrow and Stable Single Photon Emission from Dibenzoterrylene inpara‐Terphenyl Nanocrystals

Abstract: Single organic molecules are promising photon sources for quantum technologies. In this work we show photon emission from dibenzoterrylene, a widely used organic emitter, in a new host matrix, para‐terphenyl. We present a reprecipitation growth method that produces para‐terphenyl nanocrystals which are ideal for integration into nanophotonic devices due to their small size. We characterise the optical properties of dibenzoterrylene in nanocrystals at room and cryogenic temperatures, showing bright, narrow emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Solid-state quantum emitters need a high degree of order in their environment because their intrinsically narrow optical transitions can be easily perturbed by atomic, molecular, or other nanoscopic dynamics in their surroundings, leading to frequency broadening and instability. 37 This requirement is typically very difficult to satisfy when emitters are placed close to material interfaces, e.g., in thin films or in nanocrystals. In our current work, we have characterized micro-and nanocrystals produced by electrohydrodynamic dripping with the advantage that individual crystals can be printed at a desired location, e.g., on a photonic circuit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid-state quantum emitters need a high degree of order in their environment because their intrinsically narrow optical transitions can be easily perturbed by atomic, molecular, or other nanoscopic dynamics in their surroundings, leading to frequency broadening and instability. 37 This requirement is typically very difficult to satisfy when emitters are placed close to material interfaces, e.g., in thin films or in nanocrystals. In our current work, we have characterized micro-and nanocrystals produced by electrohydrodynamic dripping with the advantage that individual crystals can be printed at a desired location, e.g., on a photonic circuit.…”
Section: Discussionmentioning
confidence: 99%
“…Solid-state quantum emitters need a high degree of order in their environment because their intrinsically narrow optical transitions can be easily perturbed by atomic, molecular, or other nanoscopic dynamics in their surroundings, leading to frequency broadening and instability . This requirement is typically very difficult to satisfy when emitters are placed close to material interfaces, e.g., in thin films or in nanocrystals.…”
Section: Discussionmentioning
confidence: 99%
“…The search for new host–guest systems has been continued. Schofield et al reported a new guest–host system, DBT in para -terphenyl crystal, which allowed an easy and controlled sample preparation for nanocrystal growth . Moradi et al investigated a new guest–host system, DBT in DBN discussed earlier, which demonstrated a strong linear Stark effect .…”
Section: Past and Recent Developments In Cryogenic Single-molecule Fl...mentioning
confidence: 99%
“…Impurities could also pile up at the crystal boundaries due to expulsion from the bulk or by adsorption from the environment and contribute to a local increase of conformational states. Despite these surface-induced effects on 0-0 ZPLs, it has been possible to reduce the dimensions of host-guest crystals and yet obtain near-lifetime-limited emission in the bulk of aromatic nanocrystals <100 nm thick, grown by reprecipitation from solution 12 , 13 . Thinner matrices for single molecules are highly desirable for applications such as single-charge sensing, which requires a close proximity of the sensing molecule to the charge 14 , or potential applications in nanophotonics 15 .…”
Section: Introductionmentioning
confidence: 99%